Vascularized subcutaneous human liver tissue from engineered hepatocyte/fibroblast sheets in mice. (October 2015) - Sakai, Yusuke; Yamanouchi, Kosho; Ohashi, Kazuo; Koike, Makiko; Utoh, Rie; Hasegawa, Hideko; Muraoka, Izumi; Suematsu, Takashi; Soyama, Akihiko; Hidaka, Masaaki; Takatsuki, Mitsuhisa; Kuroki, Tamotsu; et al.
Abstract: Subcutaneous liver tissue engineering is an attractive and minimally invasive approach used to curative treat hepatic failure and inherited liver diseases. However, graft failure occurs frequently due to insufficient infiltration of blood vessels (neoangiogenesis), while the maintenance of hepatocyte phenotype and function requires in vivo development of the complex cellular organization of the hepatic lobule. Here we describe a subcutaneous human liver construction allowing for rapidly vascularized grafts by transplanting engineered cellular sheets consisting of human primary hepatocytes adhered onto a fibroblast layer. The engineered hepatocyte/fibroblast sheets (EHFSs) showed superior expression levels of vascularization-associated growth factors (vascular endothelial growth factor, transforming growth factor beta 1, and hepatocyte growth factor) in vitro . EHFSs developed into vascularized subcutaneous human liver tissues contained glycogen stores, synthesized coagulation factor IX, and showed significantly higher synthesis rates of liver-specific proteins (albumin and alpha 1 anti-trypsin) in vivo than tissues from hepatocyte-only sheets. The present study describes a new approach for vascularized human liver organogenesis under mouse skin. This approach could prove valuable for establishing novel cell therapies for liver diseases.